Bodies Creating Meaning on Stage, and on Screen: Imágina (2010), a Unique Trans-Medial Challenge - Salas Murillo, Bértold (2020)
The feature film Imágina (2010), by Adrián Cordero and Roberto Peralta, exemplifies a transmedial operation that has been little explored by Costa Rican creators: that which translates the forms and contents of a dance show, conceived for the scene, to an audiovisual entity whose temporality and spatiality are conceived for the screen. Cordero y Peralta’s video dance “transposes" three works by coreographer Rogelio López: Prohibido arte en el bosque, Cuerpos de la barra and Tributo a María Cristina (2007-2010). The transposition had the participation of the same choreographer, as well as the dancers of the Danza Abierta group, who were part of the stage version of the creations. With the cinematographic text as a starting point, this article examines the transmedial process that made it possible. In other words, an operation constituted by the meeting and dialogue of two media with their particular materials, codes, conventions and potentialities. The examination draws attention to the exchanges and tensions that emerge from the concurrence of professionals from two different disciplines. The productivity of this media and disciplinary difference is finally recognized in Imágina.